Regulação do crescimento de pimenta biquinho vermelha (Capsicum chinense) visando seu uso em ornamentação - Morales, Beatriz Romanini (Universidade Federal de São Carlos, 2025)
One of the sectors of the Brazilian flowers and ornamental plants market that is booming is the decoration of internal spaces with potted plants. However, some species that have attractive ornamental characteristics are medium to tall, not adapting to cultivation in small pots, as the case of the Biquinho Vermelha pepper. One of the alternatives to reduce plant size is through the use of the growth regulator, paclobutrazol (PBZ). This work aimed to determine the effect of PBZ concentrations and application protocols on the ornamental quality and overall preference of plants. PBZ was applied in five concentrations by three different protocols. At commercial maturity, the plants were evaluated by various plant growth parameters regarding their size and characteristics of their crown, fruits and leaves, in addition to sensory analysis using the global preference test. PBZ produced plants with darker green leaves and its direct application, regardless of the time of application, was more effective in modulating plant growth parameters compared to application via immersion. Despite this, the sensory analysis showed a greater preference among evaluators for plants in which PBZ was applied in low concentrations (2.5 and 5 mg L-1) applied directly 30 days after transplanting or through immersion of the root/substrate system in the solutions. The application of PBZ directly to the cultivation substrate, during transplantation, cannot be recommended because, in addition to the lower overall preference, the plants contained a reduced number of fruits and these were smaller in length, which harmed the ornamental value of the plants. Thus, the application of paclobutrazol via or via direct application 30 days after transplanting at concentrations of 2.5 and 5 mg L-1 produced Biquinho Vermelha pepper plants with attractive ornamental characteristics, which could be a market alternative for producers of potted ornamental plants in addition to traditional growth control methods.
Growth regulation of biquinho vermelha pepper (Capsicum chinense) for its use in ornamentation
Keywords: Paclobutrazol; Capsicum chinense; Plantas ornamentais; Regulador de crescimento; Ornamental plants; Growth regulator; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS